138 Natural history of atrial fibrillation and atrial fibrillation ablation in patients undergoing percutaneous atrial septal defect closure. (May 2019) - Carpenter, Alexander; Crowther, Oliver; Gall, Alexander; Elgamal, Sarah; Bennett, Richard; Mehisen, Mohamed; Turner, Mark; Nisbet, Ashley
Abstract : Introduction: Atrial septal defects (ASD) often co-exist with atrial fibrillation (AF). Current thinking suggests AF burden may be improved by ASD closure and that catheter interventions should occur before closure to minimise procedural risks. There are few published studies investigating the natural history of AF or ablation outcomes in ASD patients. Methods: We undertook a retrospective observational study of all percutaneous ASD closure procedures over a 12-year period. Demographic and procedural data were collected. Patients with insufficient documentation were excluded. Outcomes at one year follow-up were collected, including death, freedom from AF (office ECG and symptom-led Holter) and stroke/transient ischaemic attack (TIA). Statistical analysis was undertaken using a two-tailed Fisher's exact T-test. Results: From April 2005 to May 2017, 384 percutaneous ASD closures occurred, with 21 excluded from our dataset due to incomplete data. 69% of patients were female, with a median age of 49 (range 16–84). 88% of patients had only a single defect. 96% of procedures were acutely successful, with 3% repeat procedures. Some residual leak was seen in 10%. 64% had follow-up data at one year: all were alive with 1% incidence of stroke/TIA. 74 (20%) of the cohort had AF prior to closure, in whom 15 (20%) underwent AF ablation (40% paroxysmal, 60% persistent). 11 (73%) were ablated prior to closure. Overall, 80% of the ablation cohort were free from AF at one year with no strokes/TIA, with 100% (N=6/6) success in the paroxysmal group (67% in the persistent group N=6/9; p=0.49). There was no significant difference with AF ablation prior to closure: 82% AF-free at one year, versus 75% AF-free in the ablation after closure group, (p=1). Of those AF patients who did not undergo ablation, 36% were AF-free at one year following closure. Of 289 patients (80%) without any pre-existing AF, rates of progression to AF by one year were remarkably low, with only a single patient receiving a new diagnosis (0.3%). Conclusions: Our data demonstrate favourable short and long-term outcomes supporting ASD closure as a safe intervention with a low failure rate. We characterise the prevalence of AF in this cohort including the natural history with and without ablation. AF ablation enjoys 1-year success rates comparable to a non-ASD closure population. There is a signal, though non-statistically significant, that ablation for paroxysmal AF enjoys increased success rates. Interestingly, we see that following closure, there may be a degree of regression of AF in those even without ablation. We observed very low rates of new AF diagnoses in the follow-up period. Our cohort represents a real-world experience of several hundred consecutive patients undergoing ASD closure over more than a decade, and provides a significant new body of data in a field where many mechanistic and therapeutic questions remain unanswered. Conflict of Interest: Nil